The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1752-0606.2009.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Universal Screening for Intimate Partner Violence: A Systematic Review

Abstract: Intimate partner violence (IPV) is known to be prevalent among therapy-seeking populations. Yet, despite a growing understanding of the dynamics of IPV and of the acceptability of screening, universal screening practices have not been systematically adopted in family therapy settings. A rapidly growing body of research data-almost entirely conducted in medical settings-has investigated attitudes and practices regarding universal screening for IPV. This article is a systematic review of the IPV universal screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 78 publications
1
66
0
2
Order By: Relevance
“…There is much debate over the effectiveness of universal screening and fear of unintended consequences (40,41). Yet, research has indicated that screening increases disclosures of violence among patients and that most women and victims of DV endorse screening when it is conducted in a nonjudgmental and supportive environment that provides informed consent and ensures privacy (41).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is much debate over the effectiveness of universal screening and fear of unintended consequences (40,41). Yet, research has indicated that screening increases disclosures of violence among patients and that most women and victims of DV endorse screening when it is conducted in a nonjudgmental and supportive environment that provides informed consent and ensures privacy (41).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, research has indicated that screening increases disclosures of violence among patients and that most women and victims of DV endorse screening when it is conducted in a nonjudgmental and supportive environment that provides informed consent and ensures privacy (41). Physicians in states that have legislation that requires mandatory reporting of DV may be afraid of liability issues and/ or are concerned that patients who disclose violence may be forced into the legal process where they may be revictimized (40); however arresting and charging the abuser may be the only way to ensure the safety of the victim and her children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations